“My goal is to make sustainability mainstream”: emerging visual narratives on the environmental crisis on Instagram - San Cornelio, Gemma; Martorell, Sandra; Ardèvol, Elisenda (Frontiers in Communication, 2024)
In the face of the current climate crisis, environmental communication can contribute to providing new frames of understanding and promoting social change and positive citizen action. Through social media, on platforms like Instagram, concerned citizens embrace environmental communication activism ultimately reshaping the narratives regarding the climate crisis. These individuals, who we identify as both activists and environmental influencers, are challenging the established media narratives with their posts and stories, thus offering alternative narratives. Accordingly, this paper aims to elaborate an incipient characterization of a communicative agenda that includes the emerging elements of these visual narratives in social media as potentially able to engage citizens to take action in their ordinary lives. Our research draws on a qualitative methodological approach, based on: (1) a digital ethnography carried out on 60 Instagram accounts devoted to the dissemination of environmental concerns and contents; (2) a visual narrative analysis of 281 selected posts of the previous accounts (3) 14 in-depth interviews conducted with digital activists. As a result, we have identified the main traits of these emerging visual narratives: the use of positive visuals and content; first-person accounts highlighting the small actions and achievements (propositive narratives) that can be carried out in our daily lives; and/or the use of memes, humor, and other elements of popular culture to make the environmental cause mainstream.